President Mahmoud Abbas’ Speech about Unilateral Recognition of Jerusalem: A Semantic-Pragmatic Study - Azmi, Hasrul; Muta'ali, Abdul (Proceedings of AICS - Social Sciences, 2018)
The research is based on Palestinian President Mahmoud Abbas' political speech at the Organization of Islamic Cooperation Summit on December 13, 2017 in Istanbul, Turkey containing semantic and pragmatic elements. The study aims to describe and discover the use of semantics and pragmatic speech acts used by President Mahmoud Abbas in his speech of OIC Summit 2017. This research uses qualitative method with descriptive approach. While the theory is used as a foundation in the theory of semantic relation and the theory of speech act Searle (1979). The results of this study indicate that speech acts used by President Mahmoud Abbas in his speech cannot be separated from the context of the problems faced by the Palestinians after US President Donald Trump declared Jerusalem as the capital of Israel. Based on a speech, the authors successfully identified 44 propositions containing semantic and pragmatic elements that have been reviewed. From the findings, 35 propositions contained an act of illustrative speech and the majority of them were expressive speech acts with 19 propositions. This shows the fact that President Mahmoud Abbas and the Palestinians are only able to express the form of condemnation and the inability of their nation in facing the US unilateral decision. In addition, at least the declarative speech in the speech with a proposition indicates that Palestine has not been able to declare itself as an independent nation over the occupation of Israel.Keywords:Mahmoud Abbas, semantics, pragmatics, speech act.